Variability and predictability of performance times of elite cross-country skiers - Spencer, M.; Losnegard, T.; Hallén, J.; Hopkins, W. G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The variability in performance of elite athletes between competitions provides useful information for research on factors affecting medal-winning performance (Hopkins et al., 1999). The aim of this study was to estimate the variability of performance of cross-country skiers in international competitions. Methods: Official race times and course information were downloaded from fis-ski.com for individual-start races in World Cup, World Championship and Olympic competitions from 2001 to 2010. The eight events were classic and free versions of women`s distance (10 km), men`s distance (15 km), and men`s and women`s sprint qualification (prolog), each with a total of 410-569 athletes competing in 1-44 races at 15-25 venues. In analyses restricted to the top 10 from each race there were 55-107 athletes in 1-28 races. A linear mixed model of logtransformed race times for each event provided estimates of within-athlete race-to-race variability (the residual, expressed as a coefficient of variation, CV) after adjustment for fixed effects of snow conditions (6 levels), altitude (2 levels), and race length (simple numeric), with random effects (expressed as CV) representing differences in performance time arising from race terrain, athlete ability, and changes in-athlete ability between seasons. Predictability of performance was expressed as an intraclass correlation representing the mean correlation between pairs of races within a season. Results: Within-athlete race-to-race variability in performance time was similar for men and women in the various events for all athletes (CV of 1.5-1.8%), but for top-10 athletes men were a little less variable (0.68-0.73%) than women (0.88-1.0%). Observed effects of differences in snow conditions and altitude on mean performance time were substantial (up to ~2%) but mostly unclear, owing to extremely large effects of terrain (CV of 4-10% in top-10 analyses). Predictability of performance was extremely high (correlations of 0.90-0.96) for all athletes but only poor-moderate (0.09-0.46) for top-10 athletes. Discussion: The race-torace variability of the best skiers is similar to that of elite runners (Hopkins, 2005) and is therefore likely a consequence of irreducible variability in physiological power output, with little contribution from variability in pacing, skill, or environmental effects. Estimates of the smallest worthwhile performance enhancement (0.3x within-athlete variability) will assist researchers investigating factors affecting performance of elite skiers.